2019
DOI: 10.1007/s11064-019-02844-y
|View full text |Cite
|
Sign up to set email alerts
|

The Struggle to Make CNS Axons Regenerate: Why Has It Been so Difficult?

Abstract: Axon regeneration in the CNS is inhibited by many extrinsic and intrinsic factors. Because these act in parallel, no single intervention has been sufficient to enable full regeneration of damaged axons in the adult mammalian CNS. In the external environment, NogoA and CSPGs are strongly inhibitory to the regeneration of adult axons. CNS neurons lose intrinsic regenerative ability as they mature: embryonic but not mature neurons can grow axons for long distances when transplanted into the adult CNS, and regener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 146 publications
(129 reference statements)
0
72
0
Order By: Relevance
“…Previous results showed that Nystatin increases axon regeneration post-axotomy in primary cell cultures of hippocampal neurons (Roselló-Busquets et al, 2019). The ability of axons to regenerate is lost in adult CNS neurons (He and Jin, 2016;Curcio and Bradke, 2018;Fawcett, 2019). Primary CNS neuronal cultures lose their regenerative capacities during their in vitro differentiation (del Rio and Soriano, 2010).…”
Section: Nystatin Increases Axon Regeneration In Immature and Differementioning
confidence: 99%
“…Previous results showed that Nystatin increases axon regeneration post-axotomy in primary cell cultures of hippocampal neurons (Roselló-Busquets et al, 2019). The ability of axons to regenerate is lost in adult CNS neurons (He and Jin, 2016;Curcio and Bradke, 2018;Fawcett, 2019). Primary CNS neuronal cultures lose their regenerative capacities during their in vitro differentiation (del Rio and Soriano, 2010).…”
Section: Nystatin Increases Axon Regeneration In Immature and Differementioning
confidence: 99%
“…Axonal regeneration in the CNS is inhibited by several inhibitory molecules released in the CNS microenvironment after injury. Among these, chondroitin sulphate proteoglycans (CSPGs) are released by glia cells, myelin associated glycoprotein (MAG) by myelinating glia and oligodendrocyte myelin glycoprotein (OMgp) by oligodendrocytes [136]. Furthermore, astrocytes become reactive producing a glial scar following neuronal cell death induced by injury [137].…”
Section: Egfr Functions After Injury and Its Role In Regenerationmentioning
confidence: 99%
“…Studies aimed at enhancing CNS regeneration have identified transcriptional and epigenetic programs 6,7 , signalling pathways [8][9][10] , the cytoskeleton [11][12][13][14] and axon transport [15][16][17][18][19] as important factors governing regenerative ability. However, the precise machinery required to reconstitute and extend an injured axon is not completely understood, and repairing the injured CNS remains a challenging objective 20 .…”
mentioning
confidence: 99%